Covid-19 Research Trends In Islamic Finance: A Bibliometric Analysis - Syadiyah Abdul Shukor; Junaidah Abu Seman (Universal Publishers - Boca Raton, Florida, USA, 2024)
Global Business and Management Research: An International Journal Vol. 16, No. 3s (page:3-21)